2017
DOI: 10.15761/fsc.1000115
|View full text |Cite
|
Sign up to set email alerts
|

Is north Indian population changing it craniofacial form? A study of secular trends in craniometric indices and its relation to sex and ancestry estimation

Abstract: Objectives: Ancestry and sex estimation using craniometric indices is an important aspect of skeletal identification process, as it limits the number of antemortem records used to compare with a postmortem profile and establish a positive identification. These indices are also affected by secular or temporal changes. So the aim of the study to explore the usefulness of indices for sex and ancestry estimation in North Indian population and effect of secular changes on these indices. Materials and methods:In pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…This peculiarity made the index suitable as a racial character. 10 A study done by Eroje et al 23 reported cephalic index for Obia male and female as 73.7 and 72.2 respectively which were almost similar to the present study. In contrast, the mean cephalic index for the male and female were 81.81 and 82.99 respectively among Thai population.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This peculiarity made the index suitable as a racial character. 10 A study done by Eroje et al 23 reported cephalic index for Obia male and female as 73.7 and 72.2 respectively which were almost similar to the present study. In contrast, the mean cephalic index for the male and female were 81.81 and 82.99 respectively among Thai population.…”
Section: Discussionsupporting
confidence: 89%
“…25 A study done by Saini et al in North Indian state, Uttar Pradesh also reported dolicocephalic type of head to be the most common type. 10 In contrast it was recorded as the least common type among Nepalese Medical students of all the three ethnic groups namely Brahmin, Newar and Chettri. 26 It was the least common among (4.32%) Thai 24 and Japanese populations as well.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Uncited reference Q6 Saini et al, 2017 . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 YJHEV2638_proof ■ 17 July 2019 ■ 14/15…”
Section: Discussionmentioning
confidence: 99%
“…All of the series also include faces that vary from very broad to narrow in relation to their height, with orbits that vary from broad to very tall and nasal apertures that vary from narrow to very broad. Comparable results were found in all of these aspects by Saini et al (2017) in their study of adult Indian crania from two medical institutions (not covered by Raghavan et al 2013) in the Hindi-speaking state of Uttar Pradesh.…”
Section: Introductionmentioning
confidence: 75%